Pengaruh Literasi Digital terhadap Employability dengan Efikasi diri sebagai Mediasi pada Alumni Peserta Pelatihan Kompetensi Kerja - Diana, Rezi Delvia; Fahmy, Rahmi; Rivai, Harif Amali (Jurnal Informatika Ekonomi Bisnis, 2025)
Employability is a person's work readiness in entering the job market and the world of work. In work readiness, skills needed by the world of work are needed, these skills will support job seekers and those who are new to work to be ready in the world of work. This study is to analyze the influence of digital literacy which includes the ability to use information and communication technology effectively. Self-efficacy or individual confidence in their ability to achieve goals is expected to mediate the relationship between these variables and employability, namely the ability to get and maintain jobs. Through a survey conducted on 175 respondents from alumni of BPVP Padang training participants in 2023, research data processing was carried out using the SEM (Structural Equation Modeling) method, with the type of Structure Equation Modeling (SEM) used, namely Smart PLS. The results of the study showed that digital literacy has a direct effect on employability, but is not mediated by self-efficacy. This finding indicates the importance of digital literacy to increase employability.